2004
DOI: 10.1002/cncr.20695
|View full text |Cite
|
Sign up to set email alerts
|

Defining the best available treatment for neurocytomas in children

Abstract: BACKGROUND.In children, neurocytomas are extremely rare tumors in the central nervous system. Since this entity was introduced in 1982, approximately 60 cases have been reported among patients age Յ ϭ18 years of age. The current analysis was performed to define the best available neurocytoma therapy in children. METHODS.All reported neurocytoma cases were reviewed for age, extent of resection, radiotherapy, radiotherapy dose, local control, and survival. Data were obtained from the literature and the authors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…Complete surgical excision is currently considered as the optimal treatment for EVN, but is often limited by tumor proximity to eloquent areas ( 20 ). In cases of incomplete resection, available data suggests that radiotherapy offers the same tumor control rates for EVN ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete surgical excision is currently considered as the optimal treatment for EVN, but is often limited by tumor proximity to eloquent areas ( 20 ). In cases of incomplete resection, available data suggests that radiotherapy offers the same tumor control rates for EVN ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative radiation therapy may be effective in reducing tumor size and recurrence rates in cases of aggressive atypical neurocytoma; the recommended dose of 50 Gy is considered to be the most appropriate for long-term local control in children ( 20 ). Additional Gamma Knife stereotactic radiosurgery may be performed post-surgery in order to obtain improved local control and a higher survival rate for cases that cannot be surgically resected ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patient, a 31-years old female, started to complain of mild headache and paroxysmal diplopia about one month before admission. Therefore, she underwent brain Magnetic Resonance Imaging (MRI) scan that showed the presence of a Complete surgical resection is currently the "gold standard" treatment [10], in cases of sub-total removal, radiotherapy may be a valid alternative to control tumor growth [11]. To date, no supported data can be found about radiosurgery rate of activity on EVNs.…”
Section: Case Reportmentioning
confidence: 99%
“…Gross-total resection can be achieved in 60 to 100% of patients and recurrence is seen in up to one third of patients after subtotal resection [4,5,30,31]. Rades et al [32] found that radiotherapy after subtotal tumor removal significantly improved local tumor control but had no effect on survival of children. However, control of tumor growth is an important determinant of prognosis, because neurocytomas may have malignant behavior, for example craniospinal dissemination or intraventricular hemorrhage, at the time of recurrence.…”
Section: Introductionmentioning
confidence: 97%